INTERAKSI SOSIAL DALAM BENTUK KERJASAMA DAN PERSAINGAN ANTAR PEDAGANG DAGING SAPI DI PASAR FLAMBOYAN - Fatimah, Siti; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research was "Social Interaction in the form of cooperation and competition between Beef Traders in the Flamboyan Market". The purpose of this study was to find out how social interaction in the form of cooperation and competition among fellow beef traders in the Flamboyan Market. The method used was a qualitative method with descriptive analysis. Data collection tools were used observation guidelines, interview guidelines, and documentation tools. The results showed that: 1) Cooperation among traders in the form of harmony among fellow beef traders that fellow traders help each other without expecting anything in return. The form of harmony in helping helps was to look after each other's shanties, helping to prepare shanties, showing goods to other traders and selling their wares. 2) Cooperation between traders in the form of bargaining between beef traders that there was exchange of goods in the form of money without any agreement from fellow traders. 3) The form of competition that occurs within the trader’s environment was economic competition. Competition in attracting consumers becomes a concrete form of competition in the form of competition in service, quality of goods and forms of inventory available in shanties.Key words: Beef Traders , Competition, Cooperation, Social Interaction